Development of Dengue Fever Prevention and Control Model - Artwanichakul, Koraphat; Thiengkamol, Nongnapas; Thiengkamol, Tanarat (Mediterranean Journal of Social Sciences, 2012)
The objective of this research was to develop dengue fever prevention and control model. The populations were community health leader of Nongkhai Province. The questionnaire was used as instrument for data collecting. Pearson Correlation and Path Analysis were used for data analysis.The results revealed that environmental education in terms of knowledge (KN) showed directly affected to inspiration of public mind in aspects of role model (RM), impressive environment (IE), and impressive environment (IV) with .553, .572, and 627. Public mind in aspects of role model (RM), impressive environment (IE), impressive environment (IV) showed directly affected to participation of Dengue fever prevention and control (PAR) with .559, .608 and .516. KN also directly affected to PAR with .612. Environmental education in terms of awareness (AW) showed directly affected to RM, IE, and IV with .612, .558 and .601. AW also directly affected to PAR with .635. KN and AW showed directly affected to Dengue fever prevention and control behavior (BEH) with .544 and .653. RM, IE, and IV showed directly affected to BEH with .462, .537 and .542 respectively.